The Connection - House Survey on the Ground Floor Zone of Multi-Family Apartment - Xu, Ningxin (My University, 2020)
In a multi-family housing, ground floor together with the surrounding space, which is called the ground floor zone, is the place where residents go through every day. This area works as a “buffer zone” between indoor and outdoor, private and public space. To some extent, there are various intersections happening within it, including different people and environments. The thesis focuses on the typologies of the ground floor zone in multi-family apartment in Gothenburg, and how it changes in different time, location and housing typologies. The aim of this thesis is to explore the ground floor zone as a connection and discover the possibility to provide a more desirable transition space by design of the ground floor zone of housing. By literature research, case study and also comparisons between them, this thesis will come out with a chronology of the ground floor zone of multi-family apartment in Sweden by the analysis of space attribute of different functions. Based upon this analysis, a further research will be carried out to look at the ground floor zone of apartments with different typologies and in different locations specifically. The result will be the analysis of ground floor zone of multi-family apartments with different typologies and in different locations.
Keywords: House survey, Ground floor zone, Chronology, Typology, Location, Multi-family apartment